Presentación. - Quezada Abad, César (My University, 2015)
From the Technical University of Machala (UTMach) we are pleased to present to you the First Edition of the Scientific Journal Cumbres, a product of the effort, discipline and work mystique of the Research Center of our institution. My first congratulations are addressed to this group of people, because behind the scenes, extensive, arduous and anonymous work occurs that only information managers and coordinators know about. For this reason, I can attest that we have managed to publish a journal of academic quality, whose preparation had as antecedents: the selection of contents, layout, printing and style correction. Thus, this edition includes scientific articles which have as authors to teachers of technical and humanistic careers in the country, who from their different domains of knowledge and professional expertise have contributed with varied and rich reflections, experiences, case studies and research proposals that ultimately seek to transform society from the academy .
Desde la Universidad Técnica de Machala (UTMach) nos complace presentar a ustedes la Primera Edición de la Revista Científica Cumbres, producto del esfuerzo, disciplina y mística de trabajo del Centro de Investigaciones de nuestra institución. A este grupo humano van dirigidas mis primeras felicitaciones.Y es que detrás de bastidores, ocurre un trabajo extenso, arduo y anónimo que solo los gestores y coordinadores de la información conocen. Por ello, puedo dar fe que hemos logrado publicar una revista de calidad académica, cuya elaboración tuvo como antecedentes: la selección de contenidos, diagramación, impresión y corrección de estilo.Es así que en la presente edición se incluyen artículos científicos los cuales tienen como autores a docentes de las carreras técnicas y humanísticas del país, quienes desde sus diferentes dominios del conocimiento y experticia profesional han aportado con variadas y riquísimas reflexiones, experiencias, casos de estudio y propuestas de investigación que en última instancia buscan trasformar la sociedad desde la academia.
Keywords: UNIVERSIDAD TÉCNICA DE MACHALA; ARTÍCULOS CIENTÍFICOS